2019
DOI: 10.1109/access.2019.2914797
|View full text |Cite
|
Sign up to set email alerts
|

Twitter and Disasters: A Social Resilience Fingerprint

Abstract: Understanding the resilience of a community facing a crisis event is critical to improving its adaptive capacity. Community resilience has been conceptualized as a function of the resilience of components of a community such as ecological, infrastructure, economic, and social systems, etc. In this paper, we introduce the concept of a ''resilience fingerprint'' and propose a multi-dimensional method for analyzing components of community resilience by leveraging existing definitions of community resilience with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…The concept of resilience was first applied to the field of ecology [18]. With the continuous development of this idea, its field of application has gradually expanded to other disciplines, such as psychology [19], sociology [20], economics [21], etc. Recent studies have shown that the concept and definition of resilience can also be applied to transmission networks composed of nodes, links, and transmission services connecting them [22].…”
Section: Economic Factormentioning
confidence: 99%
“…The concept of resilience was first applied to the field of ecology [18]. With the continuous development of this idea, its field of application has gradually expanded to other disciplines, such as psychology [19], sociology [20], economics [21], etc. Recent studies have shown that the concept and definition of resilience can also be applied to transmission networks composed of nodes, links, and transmission services connecting them [22].…”
Section: Economic Factormentioning
confidence: 99%
“…Previous research into environmental disasters has shown evidence that sourcing community generated information about local action from social media and crowd-sourcing platforms is possible [23][24][25][26], and has been employed as a live data source in several natural disasters [27,28]. Posthoc analysis has also revealed that useful data can be drawn from these sources [23,29,30], including levels of community resilience [31]. These findings show simultaneously the power of the internet for connecting people and understanding the workings of communities, and subsequently the potentially dire consequences of digital exclusion that exacerbates the lack of available support for those who are most in need [32].…”
Section: Introductionmentioning
confidence: 99%
“…Volunteer and governmental agencies need timely and credible information to save lives and get access to the people affected [ 2 ]. As such, social media has become an important tool to partially understand the social perspectives and needs before, during, and after a disaster [ 3 , 4 ], and to extract first-hand information about the phases of the event.…”
Section: Introductionmentioning
confidence: 99%